Teaching and tolerance: aversive and divisive pedagogical encounters. Issue 3 (4th May 2018) - Gray, Emily
ABSTRACT: This paper takes as its subject the circulation of tolerance discourse within two pedagogical encounters in two Australian educational settings, and draws from the work of Wendy Brown on tolerance as a regulatory force. Brown argues that discourses of tolerance are produced within historical and cultural milieu that enable tolerance and aversion to exist simultaneously. This has significant implications for how we might come to understand the project of working towards a socially just educational system and the various struggles encountered within pedagogical sites. I also examine the pedagogical affects that are produced within different educational moments as we work to teach in or around difference and when we embody the Other in the classroom. I engage with how these experiences speak to the way in which tolerance as national ideal acts to both alleviate and circulate discourses of inequality such as sexism and homophobia.